Formulation and Physical Characterization of Spray Gel Containing Collagen Extracted from Catfish (Pangasius hypophthalmus) Skin - Vonny Kurnia Utama; Nabila Fitri Anugrah (LPPM Universitas Abdurrab, 2025)
Collagen is a natural protein found in vertebrate and invertebrate animals. Collagen can be found in bones, skin and cartilage. Collagen from fish skin can hold water well and does not trigger irritation, so it is very good to apply to the skin, one of which is to make a spray gel preparation. In this study, collagen was obtained from the skin extraction of catfish (Pangasius hypophthalmus). The aim of this research is to determine the effect of Na CMC concentration on the physical properties of spray gel and to determine the concentration of Na CMC that meets the requirements for spray gel preparations. The process of making collagen is carried out by soaking using 0.3% NaOH and 0.1% citric acid. Based on the research results, collagen from catfish skin produced a yield of 8.46%, collagen in powder form, grayish white. Collagen powder was formulated into 4 spray gel formulas using Na CMC as the gelling agent and varying the gelling agent concentration starting from 2 5%. The preparations formed will be evaluated. During the evaluation of the spray gel, it was found that the F1 F4 preparations met the organoleptic quality standards, homogeneity, dry time and pH. However, the viscosity and spreadability do not meet the requirements.